Chemical characterization of baby food consumed in Italy. - Maria Assunta Meli; Donatella Desideri; Davide Sisti; Ivan Fagiolino; Carla Roselli (PLoS ONE, 2024)
In this study, a total of 30 elements (essential and non-essential or toxic) were determined in 25 foods consumed in Italy by children aged 0-6 months and produced in Europe. Inductively Coupled Plasma-Atomic Emission Spectrometry and Inductively Coupled Plasma-Mass Spectrometry were used as measurement techniques for the elements of interest. The estimated intakes for one-year-old infants were compared with risk estimators and nutritional requirements. Data indicate that commercially available baby food in Italy provides an excellent contribution for Mn, Cu, Fe, Zn, Ca, K, and P, covering up to approximately 70% of the adequate intake (AI) for an infant aged 6-12 months. The intake of detectable toxic elements was always below the safety limit: even the most concentrated toxic elements never exceeded about 86% of the Provisional Tolerable Weekly Intake (PTWI). This result indicates that the analyzed baby food is of good quality and does not pose risks to children's health.